Chromosome segregation errors during early embryonic development - Hirohisa Kyogoku (Reproductive Medicine and Biology)
Abstract Background Mitosis maintains a genome's genetic information in daughter cells by accurately segregating chromosomes. However, chromosome aberrations are common during early mammalian embryogenesis. Chromosomal abnormalities during the early stages of embryogenesis result in the formation of mosaic embryos, wherein cells with normal genomes coexist with cells exhibiting abnormal genomes. The precise frequency and etiology of such abnormalities remain unclear. It is postulated that these aberrations contribute to the etiology of a number of conditions, including infertility and congenital diseases such as Down's syndrome. Methods This review synthesizes current literature and data to elucidate the causes and implications of chromosome aberrations in early mammalian embryos. It places particular emphasis on identifying patterns of mosaicism and investigating the underlying mechanisms responsible for these abnormalities. Main Findings The underlying causes of chromosome abnormalities in early embryos were examined in the context of DNA replication and embryonic development. Conclusion A deeper understanding of chromosome abnormalities in early embryos could help develop new infertility treatments and advance research on cancers caused by these abnormalities. This article reviews current knowledge and gaps in understanding chromosome segregation abnormalities during embryogenesis and future directions in this field.